1998
DOI: 10.1038/sj.onc.1201645
|View full text |Cite
|
Sign up to set email alerts
|

Human smooth muscle α-actin gene is a transcriptional target of the p53 tumor suppressor protein

Abstract: Smooth muscle (sm) a-actin is expressed in vascular smooth muscle cells and ®broblast cells. Its expression is regulated by cell proliferation and repressed during oncogenic transformation. In this study, we demonstrate that p53 activation is associated with a dramatic increase in organized micro®lament bundles and an increase in sm a-actin mRNA level. Wild-type p53, but not mutant p53, strongly stimulated human sm a-actin promoter activity in p53 null cell lines. The sequences homologous to the p53 consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
5
43
0
Order By: Relevance
“…α‐SMA is a direct transcriptional target of the tumor suppressor p53 and activation of a temperature sensitive p53 allele in rat embryo fibroblasts causes these cells to upregulate and express α‐SMA in actin filament bundles that resemble stress fibers of myofibroblasts (Comer et al, 1998). Since telomere dysfunction activates a p53 dependent DNA damage checkpoint (d’Adda di Fagagna et al, 2003; Herbig et al, 2004; Takai et al, 2003), it is possible that TGFβ1‐induced telomere dysfunction contributes to α‐SMA upregulation and transdifferentiation of myofibroblasts by promoting p53‐dependent α‐SMA expression.…”
Section: Resultsmentioning
confidence: 99%
“…α‐SMA is a direct transcriptional target of the tumor suppressor p53 and activation of a temperature sensitive p53 allele in rat embryo fibroblasts causes these cells to upregulate and express α‐SMA in actin filament bundles that resemble stress fibers of myofibroblasts (Comer et al, 1998). Since telomere dysfunction activates a p53 dependent DNA damage checkpoint (d’Adda di Fagagna et al, 2003; Herbig et al, 2004; Takai et al, 2003), it is possible that TGFβ1‐induced telomere dysfunction contributes to α‐SMA upregulation and transdifferentiation of myofibroblasts by promoting p53‐dependent α‐SMA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Sequentially activated gene transcript pro®les suggest that wildtype p53 down regulates g actin, tubulin and HSP70 gene expression (Madden et al, 1997) and Guenal et al (1997) have found that b and g actin genes are down-regulated during p53-mediated apoptosis. Others (Comer et al, 1998) have reported that p53 stimulates a-actin promoter activity, suggesting a role for p53 in cytoskeletal organization. At the protein level, indirect evidence for p53-actin interactions comes from the ®nding that actin ®lament disruption leads to p53 activation (Rubtsova et al, 1998).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, it is noteworthy to list the proteins encoded by p53 regulated genes whose function is integral to the cytoskeletal architecture. This list includes actin (Comer et al, 1998), B99 a microtubule-localized protein (Utrera et al, 1998), the recently identi®ed p53 responsive caveolin-1 (Yu et al, 1999;Stahlhut and van Deurs, 2000), cytokeratins 8 (Mukhopadhyay and Roth, 1996) and 15 (this study), Ponsin/SH3 P12/ CAP (this study), and CDCrel2b/H5/PNUTL2 (this study). In support of this proposition Gloushankova et al (1997) reported that the disruption of actin bundles following mutant ras transformation of both ®bro-blasts and epitheliocytes was reversed by expression of wild type p53.…”
Section: Gip-17mentioning
confidence: 86%